RANCANG BANGUN APLIKASI PERHITUNGAN STATS POKEMON BERBASIS ANDROID - Junius, Daniel; Syastra, Muhammad Taufik (Computer Science and Industrial Engineering, 2020)
Game development began in the 1950s when computer scientists began making games and simulations that were easy to research or just wanted to play, games that year only used lines and dots, like pong, and from that year until now, game development has been increasingly rapidly from 8-bit games like Super Mario Bros to games that use VR (Virtual Reality) and AR (Augmented Reality). However, there are only two games that have survived from the beginning until now and there are 2 descendants, namely Super Mario and Pokemon, for the purpose of this research, the Researcher will be focusing on the Pokemon franchise. The purpose of this research is to give the players information and the potential of the Pokemon the player use and also decrease the time player spent playing the game. The research method used is using the waterfall model method which includes Requirements, Design, Testing, Implementation, Verification, and Maintenance where the system design uses UML (Unified Modeling Language) diagrams which includes Use Case Diagram, Sequence Diagram, Activity Diagram, and Class Diagram. The results of this research are the Android-based Pokemon Stats Calculator program that has been successfully designed according to the demands and needs of the Players and the Researcher, the Android-based Pokemon Stats Calculator program has been built more efficiently and more effectively and can reduce various errors that occur unlike before using Microsoft Office Excel. Keywords: Android; Pokemon; UML.